The Impact of Covid19 Pandemic on Online Learning Process in the College at Southeast Sulawesi - Alchamdani Alchamdani; Fatmasari Fatmasari; Eka Rahmadani Anugrah; Nahda Putri Sari; Freddrika Putri; Astina Astina (Universitas Airlangga, 2020)
Introduction: The health crisis that occurred due to the Covid19 pandemic has an impact on the education sector. Universities in Southeast Sulawesi issued a policy to study at home during the Covid19 emergency response period. The existence of the study at home policy caused the change in the learning. The learning process cannot be done directly and is transferred through online learning. The research objective was to determine the impact of the Covid19 pandemic of the online learning process of universities in Southeast Sulawesi. Method: The type of research is a descriptive research and the technique is purposive sampling. The sample in this study were 170 students from several universities in Southeast Sulawesi. Data collection techniques by distributing the questionnaires using google form. Result and Discussion: The results show that the application of online learning is a new experience that provides convenience and flexibility in studying without having to go to campus. Regardless, online learning is still experiencing obstacles. The availability of inadequate network access resulted in unclear communication and instructions in lectures. The ability of the economy to fulfill internet quotas hinders student participation in taking online lectures. Excessive workload makes student concentration decrease. Conclusion: The government needs to ensure the availability of adequate internet network access in all regions and campuses provide subsidized internet quota for students. So, the lecture activities can be run smoothly and as expected.